A response to the proposed ELCA inter‐religious policy statement. Issue 3 (10th July 2019) - Papenfuss, Hannah
Abstract: In this solicited essay, an undergraduate Interfaith Scholar and Interfaith Studies minor at Concordia College responds to the ELCA proposed interreligious policy statement. In this essay, I will contend that the policy statement beautifully articulates our Lutheran commitment to accompany our neighbors by envisioning a world in which God celebrates all forms of diversity. Moreover, by framing our vocation in the context of relational theology, the document lays the groundwork for mutual understanding that prioritizes service to the neighbor over proselytization.